APPLICATION OF SIMULATED ANNEALING METHOD IN OPTIMIZING PROFIT-LOSS SHARING RATIO WITH VASICEK MODEL - Utomo, Prasetyo
revenue-sharing system. The revenue sharing system is meant by investors to provide investment funds to finance the manager with the share of profit and losses in accordance with the percentage of revenue share or the ratio and agreement or contract. This research applies PLS model with Musyarakah contract between investor and trader in traditional market so that investment funds are sourced from both sides. If the trader gains his profit and loss then it is borne together in accordance with the ratio and capital used. Determination of the ratio is very important to consider in optimizing the benefits of both. The method of optimization used is the Simulated Annealing (SA) methode. In this optimization, the model of the loan based on the interest system (riba) is required to be used as a benchmark. In addition, the investor also does not want the profit to be affected by inflation so that the profits gained must be greater than the inflation represented by the interest rate of Bank Indonesia. The interest rate was predicted using Vasicek Model. Therefore, the purpose of this research is to determine the value of an optimal ratio so that the investor and the trader get the optimal profit together. It needs to be done because if the ratio is too big then the investor's profit is too much but the trader gains too little and so vice versa. This research begins by retrieving data on the sales profits of the trader in the traditional market then the data is generated with the Bootstrap method so that from a little data can be used a lot to be simulated into Model of Rentenir and Model PLS. In addition, BI interest rate data from previous time is also needed to predict future BI interest rate value in September 2019 by the Vasicek method. After the various tests and simulations of MATLAB, the value of the BI interest rate predicted in September 2019 was 5.04%. The result is the investor's profit PLS (????????????????????????????????????????) smaller than the profit of the moneylender (????????????????????????????????????????) and the Profit Trader PLS (????????????????????) is greater than Trader of Moneylender (????????????????????) with the value of optimum ratio ranging between 0.0003- 0.0191 and 0.0021-0.0294.